2018
DOI: 10.1186/s12913-018-3700-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between patient-reported HIV status and provider recommendation for screening in an opportunistic cervical Cancer screening setting in Jos, Nigeria

Abstract: BackgroundCervical cancer screening (CCS) is an important health service intervention for prevention of morbidity and mortality from invasive cervical cancer. The role of provider recommendation and referral is critical in utilization of this services particularly in settings where screening is largely opportunistic. We sought to understand how patient-reported human immunodeficiency virus (HIV) infection status is associated with provider referral in an opportunistic screening setting.MethodsWe performed a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The baseline sociodemographic and cytology outcomes of the study sample has been published in an earlier related report and shown in Table 3 [22]. In brief, 85.7% of the study sample had NILM, while 9.7 and 4.6% had mild and severe cervical dysplasia respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline sociodemographic and cytology outcomes of the study sample has been published in an earlier related report and shown in Table 3 [22]. In brief, 85.7% of the study sample had NILM, while 9.7 and 4.6% had mild and severe cervical dysplasia respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The detail of the study design, setting and sample derivation for this cross-sectional analysis has been described previously [22]. In brief, we utilized de-identified data of 14,088 women who had received a CCS at the “Operation Stop Cervical Cancer ‘(OSCC) Unit in, Jos, Nigeria, over a 10-year time period (2006–2016).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed description of the study sample derivation is illustrated in Fig. 1 and in the supplementary file 1 in a previous report [ 15 ]. Also, a cross-sectional analysis of the larger primary sample from which this follow up cohort was derived has been published [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…[14] Study sample A cohort of women who had a result of negative for intraepithelial lesion or malignancy (NILM) at the rst cervical screen and had at least one follow up cytology test was included to analyze time to rst detection of an epithelial cell abnormality (ECA) and the hazard associated with such abnormalities by HIV status and other patient-reported sociodemographic characteristics. The detailed description of the study sample derivation is illustrated in Figure1 and in the supplementary le 1 in a previous report [15].…”
Section: Study Design and Settingmentioning
confidence: 99%